Edible Giblets and Bone Mineral Characteristics of Two Slow-Growing Chicken Genotypes Reared in an Organic System - Eleroğlu,H (2017)
ABSTRACT This study was conducted to compare edible giblets weight, tibial bone mineral density (BMD), and bone mineral content (BMC) of two slow-growing broiler genotypes (Hubbard S757; S757 and Hubbard Grey Barred JA; GB-JA) reared with outdoor access, and to determine the relationship between these variables. Day-old chicks (straight-run) of the genotypes S757 (n=120) and GB-JA (n=120) were housed for 98 days. Each genotype was assigned to six pens of 20 birds each. Birds were reared in indoor floor pens and moving shelters with outdoor access (during daylight hours). Absolute body (BW), heart (HW), spleen (SW), liver (LW), gizzard (GW), and abdominal fat pad (AFW) weights of the genotype S757 and male birds were statistically higher than that of the genotype GB-JA and female birds. Genotype statistically affected relative HW, whereas sex affected relative GW. Although BMD values were not influenced by genotype or sex, S757 birds and males presented statistically higher tibial BMC, lean, lean+BMC, total mass values (g) and area (cm2) compared with GB-JA birds and females. BW, HW, SW, LW, GW and AFW were positively correlated with BMC obtained by DXA. In conclusion, the measured traits influenced by genetic strain and sex. The use of the Hubbard S757 genotype in organic production systems with outdoor access is recommend.